Theology of Creation and Beauty: Kohelet 3:11 - Tibor Máhrik; Roman Králik (ESPES)
This paper explores the interrelated concepts of beauty, creation, and kitsch, which collectively form a comprehensive framework for understanding one’s relationship to the world and one’s place in it. The hermeneutic of the text Kohelet 3:11, which defines beauty as a characteristic feature of all being in the context of creation theology, is utilised to focus on the typical tension between beauty as an immanent feature of the real world and the human desire to fully understand and capture it. In this context, beauty is posited as a spiritual value that, on the one hand, reflects God’s essence and serves as a source of inspiration for humanity, and, on the other hand, remains an unattainable reality for humanity’s ambitions. This paradox forms the basis for understanding kitsch, which is not merely an aesthetic category, but also encompasses the broader cultural and value dimensions of humanity. Within the context of a narcissistic culture, kitsch is conceptualised as a manifestation of humanity’s creative endeavour to articulate beauty, characterised by a simplification of beauty that does not edify humanity and society, but rather leads to superficiality, mediocrity, and the loss of the transcendent dimension of beauty. The exploration of these three concepts in unison underscores their interconnectedness and the potential for serving as a conduit of understanding across diverse cultures, value systems, and individuals. A theology of beauty in relation to kitsch thus offers not only the possibility of reflecting on the state of the modern world, but also an important integrating element in a polarised society that can foster a deeper understanding of interpersonal relationships and the spiritual dimension of the human person.